Non-traumatic lower abdominal pain: ultrasonographic and clinical differential diagnosis - Iraklis Perysinakis; Evangelia E. Vassalou (Ultrasonography, 2024)
Lower abdominal pain is frequently reported and has a diverse differential diagnosis. In cases with atypical presentation and nonspecific findings, further imaging evaluation is required to confirm the clinical suspicion and to distinguish between self-limiting disorders and those requiring immediate intervention. In line with European guidelines, transabdominal ultrasonography is recommended as a first-line imaging modality for clinically suspected acute appendicitis and acute diverticulitis, which respectively represent the predominant causes of right and left lower quadrant abdominal pain. It is similarly the preferred method for evaluating suspected obstetric/gynecologic and genitourinary diseases. Computed tomography is utilized as a secondary option when ultrasonography results are inconclusive. This pictorial essay illustrates the sonographic features of the most common conditions associated with lower abdominal pain and outlines the clinical characteristics of each entity.